Difference Analysis of Organic Matter Enrichment Mechanisms in Upper Ordovician-Lower Silurian Shale from the Yangtze Region of Southern China and Its Geological Significance in Shale Gas Exploration. (2nd June 2019) - Wen, Ming; Jiang, Zhenxue; Zhang, Kun; Song, Yan; Jiang, Shu; Jia, Chengzao; Liu, Weiwei; Huang, Yizhou; Liu, Tianlin; Xie, Xuelian; Sun, Yue; Fan, Shichao; et al.
Abstract : The upper Ordovician-lower Silurian shale has always been the main target of marine shale gas exploration in southern China. However, the shale gas content varies greatly across different regions. The organic matter content is one of the most important factors in determining gas content; therefore, determining the enrichment mechanisms of organic matter is an important problem that needs to be solved urgently. In this paper, upper Ordovician-lower Silurian shale samples from the X-1 and Y-1 wells that are located in the southern Sichuan area of the upper Yangtze region and the northwestern Jiangxi area of the lower Yangtze region, respectively, are selected for analysis. Based on the core sample description, well logging data analysis, mineral and elemental composition analysis, silicon isotope analysis, and TOC (total organic carbon) content analysis, the upper Ordovician-lower Silurian shale is studied to quantitatively calculate its content of excess silicon. Subsequently, the results of elemental analysis and silicon isotope analysis are used to determine the origin of excess silicon. Finally, we used U/Th to determine the characteristics of the redox environment and the relationship between excess barium and TOC content to judge paleoproductivity and further studied the mechanism underlying sedimentary organic matter enrichment in the study area. The results show that the excess silicon from the upper Ordovician-lower Silurian shale in the upper Yangtze area is derived from biogenesis. The sedimentary water body is divided into an oxygen-rich upper water layer that has higher paleoproductivity and a strongly reducing lower water that is conducive to the preservation of sedimentary organic matter. Thus, for the upper Ordovician-lower Silurian shale in the upper Yangtze region, exploration should be conducted in the center of the blocks with high TOC contents and strongly reducing water body. However, the excess silicon in the upper Ordovician-lower Silurian shale of the lower Yangtze area originates from hydrothermal activity that can enhance the reducibility of the bottom water and carry nutrients from the crust to improve paleoproductivity and enrich sedimentary organic matter. Therefore, for the upper Ordovician-lower Silurian shale in the lower Yangtze region, exploration should be conducted in the blocks near the junction of the two plates where hydrothermal activity was active.